Literature Review: Pengaruh Media Pakan Terhadap Kandungan Nutrisi Black Soldier Fly (BSF) - Restu Hikmah Ayu Murti; Ananda Cinta Laura (Prosiding ESEC, 2023)
Black Soldier Fly (BSF) larvae are one type of insect that has the potential to help reduce organic waste because they can act as decomposers by converting organic waste biomass into high-quality protein. In their utilization, adult BSF larvae are often used as a component in fish and livestock feed, and the leftover maggots can be utilized as a substitute material for NPK fertilizers. The nutrient content and quality of adult BSF larvae, however, depend on the treatment received during their development, including their feeding media. This study aims to investigate the effect of different feeding media on the protein content of BSF larvae, with the goal of identifying the best treatment for BSF cultivation. The review is conducted by analyzing data from literature related to maggot feed and its nutrient content. The highest protein content, based on the collected data, is found in BSF larvae fed with a combination of 30% leftover food and 70% fruit waste, with a protein percentage of 59.25%.